2012
DOI: 10.1088/0957-4484/23/43/435706
|View full text |Cite
|
Sign up to set email alerts
|

Automated dispersion and orientation analysis for carbon nanotube reinforced polymer composites

Abstract: The properties of carbon nanotube (CNT)/polymer composites are strongly dependent on the dispersion and orientation of CNTs in the host matrix. Quantification of the dispersion and orientation of CNTs by microstructure observation and image analysis has been demonstrated as a useful way to understand the structure-property relationship of CNT/polymer composites. However, due to the various morphologies and large amount of CNTs in one image, automatic and accurate identification of CNTs has become the bottlenec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…27 Recently, the automatic detection of CNT and estimation of dispersion and orientation has been performed by measuring the tube shape characteristics with Hessian matrices for each pixel in the image. 28 This new technique enables convenient quantification of dispersion and orientation of CNT fillers and is of great use to correlate the microstructure of CNT/polymer composites and their properties with their processing conditions. In our study, the morphological study of microstructure observation by SEM was performed to determine the degree of the dispersion of CNT and understand the structure–property relationship of CNT/polymer composites.…”
Section: Resultsmentioning
confidence: 99%
“…27 Recently, the automatic detection of CNT and estimation of dispersion and orientation has been performed by measuring the tube shape characteristics with Hessian matrices for each pixel in the image. 28 This new technique enables convenient quantification of dispersion and orientation of CNT fillers and is of great use to correlate the microstructure of CNT/polymer composites and their properties with their processing conditions. In our study, the morphological study of microstructure observation by SEM was performed to determine the degree of the dispersion of CNT and understand the structure–property relationship of CNT/polymer composites.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been proposed to quantify the dispersion of CNT-polymer composites samples; most aim to measure parameters quantifying the free spacing between agglomerates, their size, and uniformity [8][9][10][11], and exploring correlations between these parameters and physical properties. Detailed low-scale observations, based on transmission or scanning electron microscopy, are time consuming and can be inaccurate due to their 2D nature [12]; recent efforts [13] have resulted in the fast construction of maps of absolute CNT concentration via optical absorbance methods, validated by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the adequate dispersion of filler in the matrix is considered a crucial factor that affects the performance of nanocomposites [39]. Mechanical and electrical properties of nanocomposite based on polymer and one-dimensional (1D) nanostructured disperse material strongly depended on the orientation of nanotubes [40,41]. Several recent research studies have focused on the influence of the nanotube alignment on the nanocomposite properties and on their applications [42,43] and have suggested that the performance of photovoltaic devices based on intrinsically conducting polymers can be improved using nanotubes as an additive to increase the crystallinity by ordering the polymer chains along the wall of the nanotube [44].…”
Section: Introductionmentioning
confidence: 99%